Liquid phase crystallized silicon on glass: Technology, material quality and back contacted heterojunction solar cells. (8th March 2016) - Haschke, Jan; Amkreutz, Daniel; Rech, Bernd
Abstract: Liquid phase crystallization has emerged as a novel approach to grow large grained polycrystalline silicon films on glass with high electronic quality. In recent years a lot of effort was conducted by different groups to determine and optimize suitable interlayer materials, enhance the crystallographic quality or to improve post crystallization treatments. In this paper, we give an overview on liquid phase crystallization and describe the necessary process steps and discuss their influence on the absorber properties. Available line sources are compared and different interlayer configurations are presented. Furthermore, we present one-dimensional numerical simulations of a rear junction device, considering silicon absorber thicknesses between 1 and 500 µm. We vary the front surface recombination velocity as well as doping density and minority carrier lifetime in the absorber. The simulations suggest that a higher absorber doping density is beneficial for layer thicknesses below 20 µm or when the minority carrier lifetime is short. Finally, we discuss possible routes for device optimization and propose a hybride cell structure to circumvent current limitations in device design.